(x - xo)^2 + (y - yo)^2 = r^2
[x - (-3)]^2 + [y - (2)]^2 = (1.5)^2
(x+3)^2 + (y-2)^2 = 2.25
Answer: option C
From the function y=x^2-4x+7
to complete the square we proceed as follows:
The vertex form is given by:
y=(x-h)^2+k
where (h,k) is the vertex:
thus from the function we shall have:
y=x^2-4x+7
c=(b/2a)²
c=(4/2)²=4
thus adding an subtracting 4 in the expression:
y=x^2-4x+4-4+7
y=(x-2)^2+3
thus the vertex will be:
(2,3)
The answer is:
<span>D. Minimum at (2, 3)</span>
Answer:
$564
Step-by-step explanation:
- Multiply $9400 by .06 - You should get $564 -
Answer:
option 2
Step-by-step explanation:
Since the sign is greater than or equal to it will be pointing to the right since it includes -9 it will be a closed circle